Impact of changing clinical practices on early blood gas analyses in very preterm infants and their associated inpatient outcomes - Huang, Hongmei; Cheung, Po-Yin; O'Reilly, Megan; van Os, Sylvia; Solevag, Anne L.; Aziz, Khalid; Schmolzer, Georg (Frontiers in Pediatrics, 2017)
Background Early studies suggest an association of abnormal carbon dioxide (PCO2) or oxygen (PO2) levels with adverse inpatient outcomes in very preterm babies. Recent resuscitation practice changes, such as targeted oxygen therapy, end-expiratory pressure, and rescue surfactant may influence these associations. Objective To assess the range of the initial partial pressures of PCO2 and PO2 in preterm neonates <33 weeks gestational age after birth and their correlation to inpatient neonatal outcomes. Study design A prospective observational cohort study of infants <33 weeks gestational age with arterial or venous blood gas analysis performed within the first hour after birth. Results One hundred and seventy infants (arterial n=75, venous n=95) with mean (SD) gestational age 28 (3) weeks and birth weight 1111 (403) g were included. None of the infants with arterial blood gases had hypocarbia (<30 mm Hg), 32 (43%) had normocarbia (30-55 mm Hg) and 43 (57%) had hypercarbia (>55 mm Hg). Seventeen of the infants with arterial blood gases (22%) had hypoxia (<50 mm Hg), 50 (67%) normoxia, and 8 (11%) hyperoxia (>80 mm Hg). In infants with venous blood samples none had venous PCO2 <40 mmHg, 41 (43%) had venous PCO2 40-60 mmHg, and 54 (57%) had venous PCO2 >60 mmHg. Multivariable logistic regression analysis showed no association of low or high PCO2 or PO2 with death or major inpatient morbidities. Conclusion With current resuscitation and stabilization practices, hyperoxia and hypocarbia was uncommon, and hypercarbia was a frequent occurrence. None of these findings correlate with adverse inpatient outcomes or death. Our findings are in direct contrast to published observations using historical practices.